(untitled) (Revista Tempo e Argumento, 2019)
This article explores how the waste crisis in Naples, which has been occurring since the 1990s, has stimulated the political creativeness of local activists who have started to experiment new ways for participation and community building. In particular, we investigate how environmental justice struggles have evolved in commoning processes (that is, in the creation of participatory institutions and in the defense of commons) by studying the social mobilization in Chiaiano, a neighborhood at the northern periphery of Naples (Italy). Using oral history interviews, documents produced by grassroots organizations, mass media reports, and our participants’ observation notes, we have analyzed the evolution of the mobilization in Chiaiano, the connections between environmental concerns and commoning, and the results in terms of social experimentation. Keywords: Environmental Justice. Commoning. Participatory Democracy. Waste. Naples (Italy).